x = 1 ∑ 1 0 x 2 + x − 4 9 + 7 ( 2 x + 1 ) i 1
If the above summation in the simplest form can be expressed as c − ( a + i b ) where a , b , c are positive integers and g cd ( a , b ) = 1 , compute a + b + c .
Clarification: i = − 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good explanation of the telescoping sum.
Nice problem.
Nice solution + Problem :-)
Great problem! Never thought about complex numbers and telescoping series :)
Problem Loading...
Note Loading...
Set Loading...
First let us try to factorize the denom. of the summation expression.
x 2 + x + ( 1 4 x + 7 ) i − 4 9 = x 2 + x + 1 4 x i + 7 i − 4 9 = x 2 + x + 1 4 x i + 7 i + i 2 4 9 ⋯ ∵ i 2 = − 1 = x 2 + x + 7 x i + 7 x i + 7 i + i 2 4 9 = x ( x + 1 + 7 i ) + 7 i ( x + 1 + 7 i ) = ( x + 7 i ) ( x + 1 + 7 i )
Now let us substitute this beautiful factorization in the summation expression:
x = 1 ∑ 1 0 ( x + 7 i ) ( x + 1 + 7 i ) 1
Now this reduces to simple telescopic summation:
x = 1 ∑ 1 0 ( x + 7 i ) ( x + 1 + 7 i ) x + 1 + 7 i − ( x + 7 i ) = x = 1 ∑ 1 0 x + 7 i 1 − x + 1 + 7 i 1 = 1 + 7 i 1 − 2 + 7 i 1 + 2 + 7 i 1 − 3 + 7 i 1 + 3 + 7 i 1 − ⋯ − 1 0 + 7 i 1 + 1 0 + 7 i 1 − 1 1 + 7 i 1 = 1 + 7 i 1 − 1 1 + 7 i 1 Multiplying numerator and denominator by the complex conjugate of the denominator , we get: = 1 2 + 7 2 1 − 7 i − 1 1 2 + 7 2 1 1 − 7 i = 5 1 − 7 i − 1 7 0 1 1 − 7 i = 8 5 0 0 1 7 0 − 1 1 9 0 i − 5 5 0 + 3 5 0 i = 8 5 0 0 − 3 8 0 − 8 4 0 i = 4 2 5 − 1 9 − 4 2 i
Hence , a + b + c = 1 9 + 4 2 + 4 2 5 = 4 8 6 .